2018
DOI: 10.1111/ijd.14332
|View full text |Cite
|
Sign up to set email alerts
|

Generalized pustular psoriasis complicated with bullous pemphigoid

Abstract: References1 Wang H, Qiao S, Zhang X, et al. A case of pyodermatitispyostomatitis vegetans. Am J Med Sci 2013; 345: 168-171. 2 Dodd EM, Howard JR, Dulaney ED, et al. Pyodermatitispyostomatitis vegetans associated with asymptomatic inflammatory bowel disease. Int J Dermatol 2017; 56: 1457-1459. 3 Mesquita Kde C, Igreja AC. Pyodermatitis-pyostomatitis vegetans: a differential diagnosis of pemphigus vegetans. An Bras Dermatol 2012; 87: 339. 4 Abellaneda C, Mascar o JM Jr, V azquez MG, et al. All that glitters is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…8 However, there are a few documented cases of simultaneous development or coexistence of GPP and pemphigoid. [3][4][5][6] Clinical and immunological features of comorbid pemphigoid in patients with psoriasis have not been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 However, there are a few documented cases of simultaneous development or coexistence of GPP and pemphigoid. [3][4][5][6] Clinical and immunological features of comorbid pemphigoid in patients with psoriasis have not been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a retrospective study of 122 patients with psoriasis vulgaris and 13 with GPP with coexisting AIBD reported that bullous pemphigoid and laminin γ1 pemphigoid were the two most frequent coexisting AIBDs 8 . However, there are a few documented cases of simultaneous development or coexistence of GPP and pemphigoid 3–6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation